E.T. Cowdrey & Co.; Drs. Pratt & Woodman; E.W. Griggs, Baker; Smith, Merrill, & Co., Oils - Sampson, Davenport, & Co. (Tufts Archival Research Center, 2005)
Page image of E.T. Cowdrey & Co.; Drs. Pratt & Woodman; E.W. Griggs, Baker; Smith, Merrill, & Co., Oils from the 1870 Boston City Directory